Improving clinical and translational research training: a qualitative evaluation of the Atlanta Clinical and Translational Science Institute KL2-mentored research scholars program. - Comeau, Dawn L.; Escoffery, Cam; Freedman, Ariela; Ziegler, Thomas R.; Blumberg, Henry M. (Journal of Investigative Medicine (Sage Publications Inc.), 2017)
A major impediment to improving the health of communities is the lack of qualified clinical and translational research (CTR) investigators. To address this workforce shortage, the National Institutes of Health (NIH) developed mechanisms to enhance the career development of CTR physician, PhD, and other doctoral junior faculty scientists including the CTR-focused K12 program and, subsequently, the KL2-mentored CTR career development program supported through the Clinical and Translational Science Awards (CTSAs). Our evaluation explores the impact of the K12/KL2 program embedded within the Atlanta Clinical and Translational Science Institute (ACTSI), a consortium linking Emory University, Morehouse School of Medicine and the Georgia Institute of Technology. We conducted qualitative interviews with program participants to evaluate the impact of the program on career development and collected data on traditional metrics (number of grants, publications). 46 combined K12/KL2 scholars were supported between 2002 and 2016. 30 (65%) of the 46 K12/KL2 scholars are women; 24 (52%) of the trainees are minorities, including 10 (22%) scholars who are members of an underrepresented minority group. Scholars reported increased research skills, strong mentorship experiences, and positive impact on their career trajectory. Among the 43 scholars who have completed the program, 39 (91%) remain engaged in CTR and received over $89 000 000 as principal investigators on federally funded awards. The K12/KL2 funding provided the training and protected time for successful career development of CTR scientists. These data highlight the need for continued support for CTR training programs for junior faculty.